Improvement of Employee Performance through Leadership Style, Readiness to Change and Competence with Work Discipline as a Moderating Variable in Indonesian Islamic Banks - Vivit Nurmasari; Rifdah Abadiyah (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this study was to determine the improvement of employee performance through leadership style, readiness to change and competence with work discipline as a moderating variable at Bank Syariah Indonesia in Mojokerto. This research is a descriptive study using quantitative methods. The technique for obtaining sampling is using the saturation sampling technique where the total population can be used as a sample, for the number of samples in this study as many as 100 respondents. In testing the data in this study using multiple linear regression techniques with IBM SPSS Statistic software version 2. The results of this study prove that the variables of leadership style, readiness to change and competence can improve employee performance with work discipline as a moderating variable in BSI Mojokerto employees.